Can blockchain link the future? - Qiao, Liang; Dang, Shuping; Shihada, Basem; Alouini, Mohamed-Slim; Nowak, Robert; Lv, Zhihan (Digital communications and networks, 2022)
Recently, decentralization has been extensively explored by researchers. Blockchain, as a representation of decentralized technology, has attracted attention with its unique characteristics, such as irrevocability and security. Consequently, herein, we introduce cutting-edge blockchain technologies from four directions: blockchain system, consensus algorithms, smart contract, and scalability. Subsequently, we analyze the current lack of consensus mechanism, fault tolerance, and block capacity of the blockchain, and the integration of blockchain into 5G/6G mobile communication. Furthermore, we discuss the possible applications of blockchain in intellectual property protection, the Internet of Things, digital twins, standardization, and epidemic prevention and control. Finally, explore the impacts and solutions of blockchain on human society beyond technology.